Implementation of the concept of social ethics in the Quran: Analytical study of tafsīr al-munīr fī al-aqīdah wa al-sharīah wa al-manhaj - Husni, Abdi Risalah; Zulaiha, Eni (Jurnal Iman dan Spiritualitas, 2025)
This study aims to analyze the implementation of social ethics concepts in the Qur'an based on Wahbah az-Zuhaili's interpretation, namely Tafsīr Al-Munīr Fī Al-Aqīdah wa Al- Shari’ah wa Al-Manhaj. The research emphasizes the identification of social ethics principles that can be applied in everyday life to build a harmonious and civilized society. The research method employs library research, with Tafsīr Al-Munīr by Wahbah az-Zuhaili serving as the primary source. The primary data consists of verses from the Qur'an and their interpretations, while the secondary data comes from books, scientific journals, and literature related to Islamic social ethics. The analysis was conducted using thematic interpretation. The results of the study show that the application of social ethics includes lowering one's voice when speaking, tabayyun (verifying the truth of news), reconciling disputing parties, being fair, and not criticizing or mocking others. These values can be used as guidelines for social behavior for individuals and society. This study is useful for the fields of religious education, interpretation studies, Islamic social sciences, character and moral development, community development, and as a practical reference for educators, scholars, policymakers, and Muslim communities who wish to apply the social ethics of the Qur'an in practice. This research highlights Wahbah az-Zuhaili's modern interpretation, which integrates aspects of faith, Shari‘ah, and social issues in understanding the social ethics of the Qur'an. This study provides a comprehensive and contextual understanding of the application of social ethical values in contemporary society, while also combining classical and contemporary interpretations to offer an innovative perspective on the study of Islamic social ethics.